Slow Self‐Assembly Favors Hysteresis above Room Temperature for an Iron(II) 1D‐Chain Spin‐Crossover Complex. Issue 5 (5th December 2012) - Nowak, René; Bauer, Wolfgang; Ossiander, Tanja; Weber, Birgit
Abstract: The X‐ray structures and magnetic properties of three new iron(II) coordination polymers with the general formula [FeL1(Lax )] n are presented. L1 is the tetradentate N2 O2 2– Schiff‐base‐like ligand ( E, E )‐dimethyl‐2, 2′‐[1, 2‐phenylenebis(iminomethylidyne)]bis(3‐oxobutanato)(2–)‐ N, N′, O 3, O 3 ′ . For the axial coordination, 4, 4′‐bipyridine (bipy), 1, 2‐bis(4‐pyridyl)ethane (bpea), and 1, 2‐bis(4‐pyridyl)ethene (bpee) were used. Spin‐transition behavior was observed for the bpea and the bipy complexes. In both cases, two different polymorphs were isolated, showing different magnetic properties. In the case of the bipy complex1, different preparation methods were tested to elucidate which conditions favor one polymorph over another. It appears that a slow precipitation of the coordination polymer favors a cooperative spin transition above room temperature, whereas a fast precipitation results in a gradual spin transition at lower temperatures. In the case of the bpea complex, an incomplete spin transition is observed, which can be explained by the crystal packing. Abstract : X‐ray structures and magnetic properties of three new iron(II) coordination polymers are presented. For two of those compounds, polymorphs with different spin transition properties were observed. The influence of different synthetic protocols on the formation of the polymorphs was investigated in detail.